RHX Dating: measurement of the Activation Energy of Rehydroxylation for Fired‐Clay Ceramics. (22nd August 2014) - Clelland, S.‐J.; Wilson, M. A.; Carter, M. A.; Batt, C. M.
Abstract : In rehydroxylation (RHX) dating, the activation energy of the rehydroxylation reaction is required first in the estimate of a material's effective lifetime temperature (ELT), and second to correct the RHX rate constant obtained at a given measurement temperature to that at the ELT. Measurement of the activation energy is thus integral to the RHX methodology. In this paper, we report a temperature‐step method for the measurement of activation energy and develop fully the underlying theoretical basis. In contrast to obtaining the activation energy from a series of separate experiments (each of which requires the sample to be dehydroxylated prior to measuring the RHX rate constant), the temperature‐step method not only requires a single dehydroxylation at 500°C but also eliminates repeated acquisition of Stage I data, which are not required for dating purposes. Since the first temperature step is set to correspond to the temperature at which a dating determination is carried out, the measurement of rate constants at higher temperatures simply becomes an extension of dating. Consequently, the logistics of obtaining the activation energy of rehydroxylation are greatly simplified.